2020
DOI: 10.1177/0956462420925250
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of 1% and 5% 5-fluorouracil creams compared with 90% trichloroacetic acid solution for anogenital wart treatment

Abstract: To evaluate the efficacy and safety of 1% and 5% 5-fluorouracil (5-FU) creams compared with 90% trichloroacetic acid (TCA) for the treatment of anogenital warts. we conducted a randomised controlled study in 72 subjects allocated to three groups: 1% 5-FU, 90% TCA and 5% 5-FU; 90% TCA was administered once a week, whereas 5-FU cream was applied three times a week. Response to therapy and side-effects were evaluated weekly for seven weeks. Evaluation at week 7 demonstrated that there was no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…In our series, at 3 months from the beginning of the therapy, complete clearance of the lesions was achieved in 53% of patients (Figures 1 and 2) and partial clearance in 35%, confirming the efficacy of 5‐FU/SAsol in the treatment of AGWs found in a previous study 5 . Other authors, evaluating the effectiveness of 5‐FU at higher concentrations (1% and 5%), found higher cure rates (respectively, 67% and 46%) after only 7 weeks 6 …”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In our series, at 3 months from the beginning of the therapy, complete clearance of the lesions was achieved in 53% of patients (Figures 1 and 2) and partial clearance in 35%, confirming the efficacy of 5‐FU/SAsol in the treatment of AGWs found in a previous study 5 . Other authors, evaluating the effectiveness of 5‐FU at higher concentrations (1% and 5%), found higher cure rates (respectively, 67% and 46%) after only 7 weeks 6 …”
Section: Discussionsupporting
confidence: 81%
“…A simplified algorithm suggests that patients with 1–5 warts should firstly be treated with ablative techniques (cryotherapy, diathermocoagulation, carbon dioxide lasers, surgery) while patients with >5 warts should use immunotherapies (imiquimod or sinecatechins cream) 2 . Other therapeutic options are destructive (salicylic acid, nitrizinc‐complex, potassium hydroxide solutions), virucidal (topical/intralesional cidofovir, intralesional interferon‐α, podophyllotoxin cream), immunotherapeutics (candida antigen injection, Bacillus Calmette‐Guérin injection, contact allergen immunotherapy) and antimitotic (podophyllotoxin cream, 5‐fluorouracil cream) 2–6 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations